Effects of Antibacterial Peptide F1 on Bacterial Liposome Membrane Integrity - Wang, Qun; Peng, Bo; Song, Mingyue; Abdullah,; Li, Jun; Miao, Jianyin; Feng, Konglong; Chen, Feilong; Zhai, Xiaoxiang; Cao, Yong (Frontiers in Nutrition, 2021)
Previous studies from our lab have shown that the antimicrobial peptide F1 obtained from the milk fermentation by Lactobacillus paracasei FX-6 derived from Tibetan kefir was different from common antimicrobial peptides; specifically, F1 simultaneously inhibited the growth of Gram-negative and Gram-positive bacteria. Here, we present follow-on work demonstrating that after the antimicrobial peptide F1 acts on either Escherichia coli ATCC 25922 （E. coli ） or Staphylococcus aureus ATCC 63589 （S. aureus）, their respective bacterial membranes were severely deformed. This deformation allowed leakage of potassium and magnesium ions from the bacterial membrane. The interaction between the antimicrobial peptide F1 and the bacterial membrane was further explored by artificially simulating the bacterial phospholipid membranes and then extracting them. The study results indicated that after the antimicrobial peptide F1 interacted with the bacterial membranes caused significant calcein leakage that had been simulated by different liposomes. Furthermore, transmission electron microscopy observations revealed that the phospholipid membrane structure was destroyed and the liposomes presented aggregation and precipitation. Quartz Crystal Microbalance with Dissipation (QCM-D) results showed that the antimicrobial peptide F1 significantly reduced the quality of liposome membrane and increased their viscoelasticity. Based on the study’s findings, the phospholipid membrane particle size was significantly increased, indicating that the antimicrobial peptide F1 had a direct effect on the phospholipid membrane. Conclusively, the antimicrobial peptide F1 destroyed the membrane structure of both Gram-negative and Gram-positive bacteria by destroying the shared components of their respective phospholipid membranes which resulted in leakage of cell contents and subsequently cell death.